Pendekatan Kontekstual dalam Pembelajaran Kitab Kanzur Roghibin Mahalli pada Bab Nikah di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Contextual Approach in Learning the Book of Kanzur Roghibin Mahalli in the Marriage Chapter at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Natasya Aurelia Ramdani; Yaasin Ilham Majid; Azhariah Azizah Fuaddy; Agil Syaifuallah (Litera Academica Publishing, 2025)
The learning of classical Islamic texts (kitab kuning) in Islamic boarding schools is an intellectual tradition deeply rooted in Indonesia's Islamic education system. One of the books studied at Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta is Kanzur Roghibin by Mahalli, particularly in the chapter on marriage (nikah). This article aims to examine the application of the Contextual Teaching and Learning (CTL) approach in the learning process of this book. Using a qualitative descriptive method through observation, interviews, and documentation, this study found that the contextual approach helps students understand fiqh material not only textually but also applicatively in daily life.